2017
DOI: 10.1094/cchem-04-17-0076-r
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Phenolics, Tocols, Antioxidant Activities, and Soluble Sugar Compositions in Red and Black Rice (Oryza sativa L.) During Boiling

Abstract: Cereal Chem. 94(5):811-819This study systematically examined hydrothermal effects of antioxidant substances, such as total phenolic (TPC), flavonoid (TFC), and proanthocyanidin (TPAC) contents, cyanidin-3-O-glucoside (C3G), peonidin-3-O-glucoside (P3G), a-, g-, and d-tocopherols, and a-, g-, and d-tocotrienols, as well as antioxidant activities, color parameters, and soluble sugar compositions in red and black rice. It showed that color differences (DE) of black rice were higher than those of red rice caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Taken together, parboiling, storage, and recooking as well as extrusion cooking can cause a loss of up to 90% of the total tocol content of rice ( 120 , 128 ). The loss of vitamin E after boiling is low, instead, an increase in the content has been reported in some cases, which is due to improved extraction after boiling ( 121 , 122 ) ( Table 6 ).…”
Section: Effect Of Cooking On the Vitamin Content Of Cerealsmentioning
confidence: 98%
“…Taken together, parboiling, storage, and recooking as well as extrusion cooking can cause a loss of up to 90% of the total tocol content of rice ( 120 , 128 ). The loss of vitamin E after boiling is low, instead, an increase in the content has been reported in some cases, which is due to improved extraction after boiling ( 121 , 122 ) ( Table 6 ).…”
Section: Effect Of Cooking On the Vitamin Content Of Cerealsmentioning
confidence: 98%
“…However, there was a notable rise in the amount of γ-tocotrienol, α-tocotrienol, γ-tocopherol, and total tocols. 118 When the cooking time is the same, the contents of total phenolic content, total flavonoid, condensed tannin, monomeric anthocyanin, cyanidin-3-glucoside, and peonidin-3-glucoside, as well as the antioxidant activities of black rice cooked by an electric hot plate cooker, are higher than those cooked by an automatic house-hold rice cooker. 119 The main reasons for the differences in polyphenol changes in black rice caused by different cooking methods are different cooking pressures and temperatures.…”
Section: Effects Of Processing Methods On Black Rice Polyphenolsmentioning
confidence: 99%
“…Folic acid losses were lower after boiling and frying compared to microwave and pressure cooking ( 129 , 130 ) while vitamin B12 losses after boiling are moderate ( 131 ). Among methods that could cause vitamin C loss, pressure cooking appears to induce the maximum loss ( 132 , 133 ). Interestingly, a study carried out on two varieties of rice showed that boiling increases antioxidant activities and the glycaemic index but does not impact on the phenolic content ( 134 ).…”
Section: Farming Methods and Processing And Their Impact On Grains Co...mentioning
confidence: 99%